TINGKAT PENGETAHUAN TENTANG KANKER SERVIKS DAN SIKAP TERHADAP DETEKSI DINI IVA PADA WANITA USIA SUBUR - Pertiwi, Latifa; Theresia, Endah Marianingsih; Widyasih, Hesty (Poltekkes Kemenkes Yogyakarta, 2016)
Early detection efforts of Cervical cancer using Visual Inspection with Acetic Acid methods that took place inWonosari II Public Health Center can not filling target with a downward trend in 2012 and 2013. Predisposition ofearly detection behavior of cervical cancer is influenced by attitude. Attitude formation process is influenced bystimulus or stimuli of one of knowledge that will be processed to produce an attitude (closed) and behavior(open). This study aim is to determine the level of knowledge about the relationship with attitudes of cervicalcancer Visual Inspection with Acetic Acid early detection on productive age woman. Type of research wasanalytic survey with cross sectional approach. Research sites was in Gatak Gunung Kidul with productive agewoman subjects aged 15-49 years whom were married with a sample 65 respondents were obtained byproportional random sampling method. Data were analyzed using chi square test. The results shows that thelevel of knowledge about cervical cancer 50.8% categorized as good, attitudes toward Visual Inspection withAcetic Acid early detection 52.3% are supportive. It can be seen from 33 productive age woman with goodknowledge have attitude that support 22 productive age woman (66.7%) and good knowledge have an attitudethat does not support as many as 11 productive age woman (33.3%). From the analysis results obtained chisquare test p-value = 0.01728 (p-value <0.05). There is a level of knowledge about the relationship withattitudes towards cervical cancer Visual Inspection with Acetic Acid early detection on productive age woman inGatak Gunung Kidul 2014.